Computed tomography hepatic arteriography has a hepatic falciform artery detection rate that is much higher than that of digital subtraction angiography and 99mTc-MAA SPECT/CT: Implications for planning 90Y radioembolization? - Burgmans, M.C. (2014)
10.1016/j.ejrad.2012.08.007